Murder walks the plank : a death on demand mystery - Hart, Carolyn G. (New York : William Morrow, 2004)
Pleased with the success of her murder-mystery cruise, Annie Darling and her husband, Max, are suddenly on the hunt for a killer when one of the cruise participants falls overboard, the first in a series of suspicious deaths.
Keywords: Ocean travel -- Fiction; Detective and mystery fiction